Influência da fraude e da clandestinidade nas perdas técnicas de energia elétrica - Donadel, Clainer Bravin (2010)
Energy losses in distribution systems have been receiving greater attention from electric power companies all over the world. In Brazil, in special, stricter loss goals are being set by the regulating agency for each year of the tariff cycle. Companies whose loss rates overpass the set limits risk having such excess unaccounted for in the tariff, having to assume the responsibility for the losses. In face of such a scenario, it is fundamental to understand loss behavior. The first step towards this is to assess the technical loss level and, conversely from the total losses, to assess the non-technical losses. This paper presents the chief existing methodologies for technical loss calculation in the distribution systems, highlighting the information level required in each one. Naturally, more precise methodologies require greater detailing of the existing electric network. Among the several methodologies presented, one stands out: the methodology presented by Meffe (2001), in EDP Escelsa implantation, based on the use of typical load curves and on the uniform adjustment of consumptions elaborated from feeder and substation measurements. As an improvement to Meffe´s methodology (2001), this paper presents an adjustment in technical loss calculation, directly taking into account information about non-technical losses. To that end, it was proposed the use of historical data of inspections carried out in the field (history of cheating consumers), both in LV consumers and in MV consumers, to estimate non-technical losses in each transformer and to differentially correct the clients´ consumption in order to adjust technical loss calculation. Next, a new methodology adjustment is proposed, so as to also consider in its calculation the influence of clandestine consumers, who are not enrolled in the concessionary database. The new methodology results are evaluated in a comparative way with Meffe´s methodology, and restrictions to its use are shown. It was found that the historical base of inspections and the withdrawal of illegal consumers must be reliable, since low quality input might significantly damage the final results.